COMMON MICROFLORA INVOLVED IN SPOILAGE OF CANNED PRAWNS - NAMBIAR, V NARAYANAN; IYER, K MAHADEVA (Fishery Technology, 2025)
An elaborate survey was carried out to ascertain the common types of micro-organisms responsible for spoilage in canned prawns. Among nearly 1,500 strains isolated from bacteriologically defective cans, 60% were Gram positive sporeformers of the Bacillus type. Other types Â·’solated belonged to Gram positive cocci, Gram negative rods, Gram positive non:::sporeforming rods, Gram negative cocci and coccoids. No anaerobe could be isolated. The predominant. Gram positive sporeformers were identified as Bacillus pantothenlicus, B. lrmusJ B. brevis and B. Pumilus species.